Visit Malaysia : Fun & food in Johor [electronic resource] - Ang Jun Qi, 1983-, author; Alex Sim Tze Huang, Dr., supervisor; Fakulti Komputeran
Project Paper (Sarjana Muda Sains Komputer (Sistem Pangkalan Data)) - Universiti Teknologi Malaysia, 2015